Human Midbrain Auditory Evoked Potentials Do Not Differ Between Bursts and Suppressions of Cortex Activity in Propofol Anesthesia: Case Report - Kantserova, Anna O.; Oknina, Lyubov B.; Masherov, Eugeny L.; Podlepich, Vitaly V.; Kamenetskaya, Maria I.; Zaitsev, Oleg S.; Pitskhelauri, David I. (International Journal of Innovative Research in Medical Science, 2020)
Propofol, the most widely administered anesthetic agent, is used for sedation and general anesthesia. During general anesthesia it can induce bursts and suppressions of cortex activity, which exact mechanism of generation has not been identified yet. The aim of study was to investigate the difference between midbrain auditory evoked potentials recorded during bursts and suppressions of cortex activity. These potentials were registered from the drainage-electrode implanted in the cerebral aqueduct of an adult patient with an obstructive hydrocephalus who had undergone pineal region tumor removal through anterior interhemispheric transcallosal approach. The cortex activity was divided into rare bursts of alpha activity (total length of 9 seconds) and prolonged suppressions (total length of 104 seconds). Midbrain auditory evoked potentials included long latency peaks with no statistically significant difference in their amplitudes and latencies between bursts and suppressions of cortex activity. The results suggest that human midbrain auditory evoked potentials do not differ between bursts and suppressions of cortex activity in propofol anesthesia. Therefore, for clear midbrain auditory evoked potentials cognitive but not the total electrical activity of the cortex should be suppressed.